Wearable communication systems and antennas for commercial, sport and medical applications - Sabban, Albert (IOP (Series). Release 6., 2018)
Discussing the importance of wearable communication devices and antennas, Dr. Sabban details the importance of such devices, their applications and the technology behind them. The author discusses techniques that will enable electrical engineers and students to study fundamental designs in basic electromagnetic, antennas, microwave and communication systems. Progressing from elementary communication, electromagnetics and antenna topics to more advanced systems that can be implemented by professionals in the field, this book provides a comprehensive insight into wearable devices, microwave technologies and antennas, their practical uses and their development.